The Effect of Work Stress and OCB (Organization Citizenship Behavior) on Turnover Intention in Employees (A Study on PT. Mustika Dharma Jaya Lamongan) - Moh. Slamet Heriyanto; Muhamad Imam Syairozi; Abid Muhtarom (Sean Institute, 2025)
Production employees at PT Mustika Dharmajaya have good job satisfaction which is reflected in their satisfaction with their fellow colleagues. All production employees who work at PT Mustika Dharmajaya have a harmonious relationship between their colleagues (such as helping each other when doing their work, having good communication when working, etc.) so that they respect and respect each other to all their colleagues. Production employees at PT Mustika Dharmajaya also have a good organizational commitment because there are many production employees who are loyal to work at PT Mustika Dharmajaya. The purpose of this study is to find out the effect of work stress and OCB (Organizational Citizeship Behavior) on Turnover Intention. The analysis method used in this study is a quantitative descriptive method with a statistical test analysis tool. The formulation of this research problem is whether Work Stress and OCB have a partial effect on Turnover Intention in employees of PT. Mustika Dharma Jaya Lamongan, Does Work Stress and OCB Simultaneously Affect Turnover Intention in Employees of PT. Mustika Dharma Jaya Lamongan, Of the two variables (Work stress and OCB) which variable has a dominant effect on turnover intention in employees of PT. Mustika Dharma Jaya Lamongan. The results of this study are from the results of the t-test for the variable Organizaton Citizenship Bihavior (X2) on Turnover Intention, the results of the significance level were obtained which were 0.177 < 0.10 and tcount of 1.370 and ttable of 1.67412. From this data, the value of tcalcul> ttable (1,370> 1,67412) was obtained. Therefore, it can be concluded that partially the variable Organization Citizenship Behavior has a significant effect on Turnover Intention. It can be seen from the results in table 5.22 that it can be concluded that the value of F is calculated as 683.377 while F of the table ɑ = 10% or 0.01 the result of F of the table is 2.30 which means that F calculates 683.377 > F table 2.30, with a significance of 0.000 < 0.1, then H0 is rejected and H1 is accepted so that there is a significant influence between the variable Work Stress (X1), OCB (X2), to Turnover Intention (Y) in Employees of PT. Mustika Dharma Jaya Lamongan.